Stress distribution in the muscles of the diaphragm (Archives of Mechanics - Test, 2000)
The diaphragm is treated as a membrane subject to a uniform pressure. The muscle action is modeled as a uniaxial active stress in the direction of muscle bundles. In the present paper we look for the generalized stress distribution in the membrane. The shape of the active diaphragm is approximated by a surface know as a cyclide. For this simplified shape, a closed form solution of the equilibrium equations is obtained.